Inpatient perception of the care provided by nursing students - Campiño-Valederrama, Sandra Milena; Duque, Paula Andrea; Cardozo-Arias, Victor Hugo (Universidad y Salud, 2019)
Introduction: Nursing has evolved its work around the theoretical constructs that compose it, this progressive growth includes the development of resignified teaching processes for future professionals, which must be validated around human responses in the nurse-patient relationship. Objective: Describe the perception of the hospitalized patient about the care provided by nursing students. Materials and methods: A quantitative, descriptive, cross-sectional study, conducted with 356 patients who received care from nursing students within health institutions. The Perception of Humanized Nursing Care instrument - version 3 was applied. It was analyzed with descriptive statistics and a non-parametric test using Kruskal-Wallis probability. Results: The patients stated that “humanized care is always perceived”, regarding the questions related to instructions on self-care; low scores were obtained in identification of physical, psychological and spiritual needs. Conclusion: It is necessary to address the issue of humanized care as a phenomenon of interest of the discipline when identifying strengths and weaknesses with studies of relevance around care.